Developments in immunosuppression. Issue 1 (February 2021) - Viklicky, Ondrej; Slatinska, Janka; Novotny, Marek; Hruba, Petra
Abstract : Purpose of review: In this review, we discuss achievements in immunosuppression in kidney transplant recipients published at last 18 months. Recent findings: Results of recent trials with everolimus in low-risk primary kidney transplant recipients suggest that low TAC/EVR combination is noninferior and CMV and BKV viral infections are less frequent to stand TAC/MPA. Iscalimab monoclonal antibody, which prevents CD40 to CD154 binding, has just recently entered phase II clinical studies in kidney transplantation. Eculizumab, anti-C5 monoclonal antobody was recently shown to improve outcomes in DSA+ living-donor kidney transplant recipients requiring pretransplant desensitization because of crossmatch positivity. Proximal complement C1 inhibition in patients with antibody-mediated rejection was studied in several phase I trials. Summary: Recent knowledge creates a path towards future immunosuppression success in sensitized recipients and in those in high risk of viral infections or CNI nephrotoxicity.